Is the sFlt-1/PlGF ratio efficient in predicting adverse neonatal outcomes in small-for-gestational-age newborns? A prospective observational multicenter cohort study - Kosińska-Kaczyńska, Katarzyna; Chaberek, Katarzyna; Szymecka-Samaha, Natalia; Brawura-Biskupski-Samaha, Robert; Czapska, Agnieszka; Żebrowska, Kinga; Dera, Norbert; Madzelewski, Jan; Góra, Jakub; Borawski, Kacper; Włoch, Weronika; Scholz, Anna (Frontiers in Medicine, 2024)
Introduction: Fetuses with growth abnormalities are at an increased risk of adverse neonatal outcomes. The aim of this study was to investigate if placental growth factor (PlGF), soluble fms-like tyrosine kinase-1(sFlt-1) or sFlt-1/PlGF ratio were efficient predictive factors of adverse neonatal outcomes in small for gestational age (SGA) newborns.Methods: A prospective observational multicenter cohort study was performed between 2020 and 2023. At the time of SGA fetus diagnosis, serum angiogenic biomarker measurement was performed. The primary outcome was adverse neonatal outcome, diagnosed in case of any of the following: <34 weeks of gestation: mechanical ventilation, sepsis, necrotizing enterocolitis, intraventricular hemorrhage grade III or IV and neonatal death before discharge; ³34 weeks of gestation: Neonatal Intensive Care Unit hospitalization, mechanical ventilation, continuous positive airway pressure, sepsis, necrotizing enterocolitis, intraventricular hemorrhage grade III or IV and neonatal death before discharge.Results: 192 women, who delivered SGA newborns were included in the study. The serum concentrations of PlGF were lower, leading to higher sFlt-1/PlGF ratio in the adverse outcome group. No significant differences in sFlt-1 levels were observed between the groups. Both PlGF and sFlt-1 had a moderate correlation with adverse neonatal outcomes (PlGF: R -0.5, p<0.001; sFlt-1: 0.5, p<0.001). sFlt-1/PlGF ratio showed a correlation of 0.6 (p<0.001) with adverse outcomes. Uterine artery pulsatility index PI and sFlt-1/PlGF ratio were the only independent risk factors for adverse outcomes. sFlt-1/PlGF ratio of 19.1 had a high sensitivity (85.1%) but low specificity (35.9%) in the prediction of adverse outcomes and the strongest correlation with them. It allowed the assessment of the risk of adverse outcomes as low with almost with 80% certainty. Discussion: sFlt-1/PlGF ratio seems to be an efficient predictive tool in adverse outcome risk assessment. More studies on large cohorts of SGA-complicated pregnancies with and without preeclampsia needed to develop an optimal and detailed formula on the risk assessment of adverse outcomes in SGA newborns.